1998
DOI: 10.1073/pnas.95.11.6337
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the chloride-bicarbonate exchanger gene AE1 cause autosomal dominant but not autosomal recessive distal renal tubular acidosis

Abstract: Primary distal renal tubular acidosis (dRTA) is characterized by reduced ability to acidify urine, variable hyperchloremic hypokalemic metabolic acidosis, nephrocalcinosis, and nephrolithiasis. Kindreds showing either autosomal dominant or recessive transmission are described. Mutations in the chloride-bicarbonate exchanger AE1 have recently been reported in four autosomal dominant dRTA kindreds, three of these altering codon Arg589. We have screened 26 kindreds with primary dRTA for mutations in AE1. Inherita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
188
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(190 citation statements)
references
References 29 publications
(26 reference statements)
1
188
1
Order By: Relevance
“…In distal RTA (dRTA), the kidney fails to produce an appropriately acid urine in the presence of systemic metabolic acidosis or after acid loading, due to impaired hydrogen ion secretion in the distal nephron. Both autosomal dominant (OMIM 179800) (1)(2)(3)(4)(5) and autosomal recessive (OMIM 602722) (6, 7) patterns have been observed in kindreds with primary dRTA, and the spectrum of clinical severity is wide. Proximal RTA (pRTA) is caused by an impairment of bicarbonate absorption in the proximal tubule (PT) and is characterized by a decreased renal HCO 3 Ϫ threshold (8).…”
mentioning
confidence: 99%
“…In distal RTA (dRTA), the kidney fails to produce an appropriately acid urine in the presence of systemic metabolic acidosis or after acid loading, due to impaired hydrogen ion secretion in the distal nephron. Both autosomal dominant (OMIM 179800) (1)(2)(3)(4)(5) and autosomal recessive (OMIM 602722) (6, 7) patterns have been observed in kindreds with primary dRTA, and the spectrum of clinical severity is wide. Proximal RTA (pRTA) is caused by an impairment of bicarbonate absorption in the proximal tubule (PT) and is characterized by a decreased renal HCO 3 Ϫ threshold (8).…”
mentioning
confidence: 99%
“…Human genetic studies have recently identified essential elements for pH homeostasis. To date, three genes in which mutations cause distal renal tubular acidosis have been identified (4)(5)(6). One of these genes, AE1, is essential for normal renal bicarbonate reabsorption.…”
mentioning
confidence: 99%
“…Two families with dominant forms of dRTA have been reported to express distinct truncation mutations in the AE1 C-terminal tail (23,24). The AE1 901X mutation was associated with normal eAE1 polypeptide abundance and function in red cells, and exhibits wild-type (wt) Cl Ϫ influx in Xenopus oocytes (25), properties shared with the dominant dRTA AE1 mutant R589H (26,27).…”
mentioning
confidence: 99%